A new arboreal frog of the genus Guibemantis from the southeast of Madagascar (Anura: Mantellidae) - Vences, Miguel; Jovanovic, Olga; Safarek, Goran; Glaw, Frank; Köhler, Jörn (Zootaxa, 2015)
We describe a new species of arboreal frog of the genus Guibemantis, subgenus Guibemantis, from low altitude rainforest in Manombo Special Reserve, south-eastern Madagascar. Previously published phylogenetic analyses of mitochondrial DNA sequences have placed Guibemantis diphonus sp. nov. sister to G. timidus. The new species is distinguished from G. timidus and all other species in the subgenus by a substantial genetic differentiation (≥ 4.4% uncorrected p-distance in the mitochondrial 16S rRNA gene), strongly divergent advertisement call, and some limited morphological differences. It is the smallest known species in the subgenus, with 34−36 mm snout-vent length in adult males. Its advertisement call is unique among other species in the subgenus in being composed of two distinctly different note types (only one note type in the other species).